PENGEMBANGAN MEDIA PERMAINAN KARTU QR-CODE UNTUK MENUMBUHKAN MINAT BELAJAR SISWA SMP TENTANG MALWARE - Anam, Shahril Choirul; Soraya, Dila Umnia; Indrasari, Novita Tri (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
Students' learning interest remains low due to the lack of instructional media that align with their characteristics. This study aims to develop a QR-Code-based card game learning media to foster students' learning interest. The research employed a Research and Development (R&D) approach using the ADDIE model. The participants were 32 eighth-grade students from a public junior high school in Malang. The media was validated by content and media experts, and tested through classroom implementation. Learning interest was measured using a questionnaire based on four indicators: interest, engagement, enjoyment, and attention. The instrument was validated through a validity test (r count > 0.349) and a reliability test using Cronbach’s Alpha (α = 0.957), indicating that the questionnaire was both valid and reliable. Data were analyzed using percentage techniques. The results showed that the media was categorized as “Feasible” (74.73%) and students’ learning interest increased to the “High” category (78.57%). Therefore, the media is effective in enhancing students’ learning interest.